2015
DOI: 10.1371/journal.pgen.1004930
|View full text |Cite|
|
Sign up to set email alerts
|

Imputation of the Rare HOXB13 G84E Mutation and Cancer Risk in a Large Population-Based Cohort

Abstract: An efficient approach to characterizing the disease burden of rare genetic variants is to impute them into large well-phenotyped cohorts with existing genome-wide genotype data using large sequenced referenced panels. The success of this approach hinges on the accuracy of rare variant imputation, which remains controversial. For example, a recent study suggested that one cannot adequately impute the HOXB13 G84E mutation associated with prostate cancer risk (carrier frequency of 0.0034 in European ancestry part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
1
37
2
Order By: Relevance
“…RPGEH participants included men in the RPGEH Genetic Epidemiology Research on Aging (GERA) cohort (dbGaP phs000674.v1.p1), as well as PCa cases with a DNA sample in the RPGEH biorepository but who were not part of GERA. These studies have been previously described (2931,41) (dbGaP phs000674.v1.p1). Briefly, the ProHealth study focused on ascertaining KP Northern California African-American PCa cases.…”
Section: Methodsmentioning
confidence: 99%
“…RPGEH participants included men in the RPGEH Genetic Epidemiology Research on Aging (GERA) cohort (dbGaP phs000674.v1.p1), as well as PCa cases with a DNA sample in the RPGEH biorepository but who were not part of GERA. These studies have been previously described (2931,41) (dbGaP phs000674.v1.p1). Briefly, the ProHealth study focused on ascertaining KP Northern California African-American PCa cases.…”
Section: Methodsmentioning
confidence: 99%
“…UNR is a cytoplasmic protein known to function as an RNA chaperone and is found to be crucial in the control of cell proliferation and death4849. The protein mainly destabilizes the c-fos mRNA and helps in the initiation and activation of cap-independent translation via the IRES for various transcripts, especially the proto-oncogene c-myc, rhinovirus, poliovirus, the cell cycle PISTLRE kinase, and pro-apoptotic factor (Apaf-1)5051. The SNP rs543028086 was predicted to result in the disruption of the UNR Binding Site (UNR_BS) motif in the 3′UTR of human HOXB13 gene, which results in the deregulation of pro-apoptotic factor (Apaf-1), which might have a negative effect on the control of cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up genotyping on the variant, at least on a subset of your individuals, can confirm if the variant imputed correctly. Ideally the correlation of the imputed genotype and the actual genotype will have a correlation similar to the estimated r 2 from imputation (e.g., the r info 2 estimate) [26]. For rare variants, it may be very useful to confirm the genotype by enriching the number of individuals who are imputed to have the rare variant, though this may slightly invent inflate the true r 2 because of enrichment.…”
Section: Performing Genotype Imputationmentioning
confidence: 99%
“…However, another study found an ancestral haplotype containing the mutation [31], suggesting that imputation might be possible. By using the hybrid imputation approach and combining 1000 Genomes Project data with an enriched set of prostate cancer cases who carried the mutation, Hoffmann and colleagues were able to successfully impute the G84E mutation into a large cohort with r 2 =0.57 (computed from a genotyped subset) [26]. Why one study was able to impute this mutation while another was not reflects the difficulty in imputing rare variants [16].…”
Section: Successful Rare Variant Imputation: Strategies and Examplesmentioning
confidence: 99%
See 1 more Smart Citation